PENGARUH PENGGUNAAN MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION(PBI)TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA MATERI TEOREMA PYTHAGORAS DI KELAS VIII SMP NEGERI 1 PADANG BOLAK JULU - Rahmatika Elindra; Annisa Rahma (JURNAL MathEdu (Mathematic Education Journal), 2019)
This study aims to know whether there is a significant influence of using PBI learning model on students’ mathematical problem solving ability on the topic Pythagoras theorem at the eighth grade students of SMP Negeri 1Padangbolak. The research was conducted for 3 months (September-October 2017) by applying experimental method (one group pretest post test) with 25 students and they were taken by using cluster sampling technique from 77 students. Observation and test were used in collecting the data. Based on descriptive analyzes, it could be found that a) the average of using PBI learning model was 3.50 (very good category), b) the average of students’ mathematical problem solving ability on the topic Pythagoras theorem before using PBI learning model was 69 (enough category) and after using PBI learning model was 88.50 (very good category). Furthermore, based on inferential statistic by using paired sample ttest and helping SPSS 16, the result showed the significant value was less than 0.005 (0.000<0.005). It means, there is a significant influence of using PBI learning model on students’ mathematical problem solving ability on the topic Pythagoras theorem at the eighth grade students of SMP Negeri 1Padangbolak. Keywords: problem based instruction (PBI) learning model, mathematical problem solving ability, Pythagoras theorem